2009
DOI: 10.3389/neuro.06.002.2009
|View full text |Cite
|
Sign up to set email alerts
|

Pausing Purkinje cells in the cerebellum of the awake cat

Abstract: A recent controversy has emerged concerning the existence of long pauses, presumably reflecting bistability of membrane potential, in the cerebellar Purkinje cells (PC) of awake animals. It is generally agreed that in the anesthetized animals and in vitro, these cells switch between two stable membrane potential states: a depolarized state (the ‘up-state’) characterized by continuous firing of simple spikes (SS) and a hyperpolarized state (the ‘down-state’) characterized by long pauses in the SS activity. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 21 publications
5
62
2
Order By: Relevance
“…In addition, our data showing similar state-dependent changes in [Ca 2ϩ ] transients under light anesthesia appear to be inconsistent with the lower prevalence of bistability in awake mice (Schonewille et al, 2006). Although this issue is still debated (Loewenstein et al, 2005;Schonewille et al, 2006;Tal et al, 2008;Rokni et al, 2009;Yartsev et al, 2009), one possible explanation is that increased background and evoked parallel fiber input in the awake state could override the hyperpolarization that represents the transition from up to down state. In that case, we would expect bistability to be modulated by wakefulness and not by anesthetic level.…”
Section: Modulation Of Dendriticcontrasting
confidence: 47%
See 2 more Smart Citations
“…In addition, our data showing similar state-dependent changes in [Ca 2ϩ ] transients under light anesthesia appear to be inconsistent with the lower prevalence of bistability in awake mice (Schonewille et al, 2006). Although this issue is still debated (Loewenstein et al, 2005;Schonewille et al, 2006;Tal et al, 2008;Rokni et al, 2009;Yartsev et al, 2009), one possible explanation is that increased background and evoked parallel fiber input in the awake state could override the hyperpolarization that represents the transition from up to down state. In that case, we would expect bistability to be modulated by wakefulness and not by anesthetic level.…”
Section: Modulation Of Dendriticcontrasting
confidence: 47%
“…We did not observe [Ca 2ϩ ] changes associated with spontaneous up-down or down-up transitions that were not triggered by CS (data not shown). In addition, given that membrane potential bistability of Purkinje cells in physiological (awake) conditions and the role of CS in state transitions are highly debated (Loewenstein et al, 2005;Schonewille et al, 2006;Yartsev et al, 2009), we questioned whether the correlation between peak amplitude of CF-triggered [Ca 2ϩ ] transients and state transitions of the cell is dependent on the depth of anesthesia. We therefore repeated the experiments under relatively light anesthesia (0.5-1% isoflurane).…”
Section: Dendritic Calcium Transients Evoked By Dendritic Camentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate performance on this task requires continuously monitoring the salient behavioral parameters and adjusting for mismatches in hand movement relative to target movement (Hewitt et al, 2011;Popa et al, 2012). This task subverts overly learned, stereotypic behaviors, such as reaching and saccades, in which movement parameters are correlated (Paninski et al, 2004;Soetedjo et al, 2008). It is possible that, during more stereotypic movements, particular aspects of the behavior dominate the CS and SS modulation with little need to adjust the information in the SS firing.…”
Section: Pseudo-random Tracking Css and Changes In Ss Encodingmentioning
confidence: 99%
“…In experiments performed in vivo and in slices, complex spikes recorded from Purkinje cells have been correlated to state changes in Purkinje cells (5,7,8,12). It has been shown that single stimuli to the parallel fibers, which originate from within the cerebellar cortex, can cause bursts of action potentials in Purkinje cells, which terminate with a brief pause in Purkinje cell firing, hypothesized to result from an increased Ca 2+ sensitive K + conductance (13,14).…”
mentioning
confidence: 99%